2009
DOI: 10.4049/jimmunol.182.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Metalloproteinase ADAM17/TNF-α-Converting Enzyme Regulates Proteolytic Shedding of the MHC Class I-Related Chain B Protein

Abstract: MHC class I-related chain (MIC)AT he MHC class I-related chain (MIC) 4 A and B proteins are polymorphic MHC-related molecules that bind the activating receptor NKG2D. Engagement of NKG2D by these ligands leads to the activation of lysis and cytokine secretion by NK cells and T cells and thus plays a central role in immune system activation (for review, see Refs. 1 and 2). The vast majority of healthy cells do not express MIC molecules and instead their expression at the cell surface is up-regulated in pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 27 publications
7
137
1
Order By: Relevance
“…Several studies, primarily performed in different types of tumor cell lines or transfected cells in steady-state conditions, indicate the direct involvement of both ADAM10 and ADAM17 enzymes in MICA and MICB release, but the relative contribution of these enzymes is still controversial. Boutet et al (32) found that ADAM17 mediates MICB proteolytic cleavage in CV1 epithelial transfectants; however, recent evidence highlights a cell type-specific role for these metalloproteinases (33). Our results also reveal high levels of ADAM10 expression in several MM cell lines and in primary malignant PCs, with enzyme expression not correlating with the disease stage.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Several studies, primarily performed in different types of tumor cell lines or transfected cells in steady-state conditions, indicate the direct involvement of both ADAM10 and ADAM17 enzymes in MICA and MICB release, but the relative contribution of these enzymes is still controversial. Boutet et al (32) found that ADAM17 mediates MICB proteolytic cleavage in CV1 epithelial transfectants; however, recent evidence highlights a cell type-specific role for these metalloproteinases (33). Our results also reveal high levels of ADAM10 expression in several MM cell lines and in primary malignant PCs, with enzyme expression not correlating with the disease stage.…”
Section: Discussioncontrasting
confidence: 53%
“…To investigate whether drug-induced MICB release involves metalloproteinase activity (32,33), we evaluated MICB levels in the supernatants of DOX-and MEL-treated SKO-007(J3) cells in the presence of the metalloproteinase inhibitor marimastat. As MICA gene typing was performed as described in Materials and Methods.…”
Section: Inhibition Of Micb Shedding On Drug-treated Cells By Treatmementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, members of the ADAM (a disintegrin and metalloproteinase) family have been identified as key proteases involved in the shedding of some alleles of MICA and MICB (21,22), and a member of the disulfide isomerase family, ERp5, has also been proposed to play a role in the shedding of MICA (23). ADAMs 10 and 17 have been shown to be involved in proteolytic cleavage of ULBP2 (22), but nothing else is known about the shedding of other ULBPs.…”
mentioning
confidence: 99%
“…Many ADAMs are overexpressed in tumors and affect different steps of tumor progression [117]. NK cell recognition of target cells is hampered by ADAM10 and ADAM17 activation, which were shown to be involved in the proteolytic release of soluble MICA and MICB from tumor cells [118,119]. Grzywacz et al suggested that NK cell encounter of target cells led to activation of MMPs that subsequently shed CD16 from the surface of NK cells [120].…”
Section: Nk Cell Recruitment To the Tumor Sitementioning
confidence: 99%